SISTEM PAKAR DIAGNOSA UNTUK MEMBANTU PROGRAM PENGONTROLAN BERAT BADAN - Wisnu Gumilang, Komang (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Useful as a decision support system that can support systems and decision support that leverages the benefits of human and electronic devices such as computers. Too much use of computers will result in a mechanical solution, a reaction that is not flexible, and shallow decisions. Whereas if you use too many men will bring a slow reaction, the utilization of the data which is too limited, and lags in reviewing the relevant alternatives. The purpose of this expert system design is to create software on weight control. Software used to build an expert system is Visual Basic 6.0. Results to be achieved in the design of this system is a software that can serve as an expert for weight control. Keywords: Expert Systems, Control Weight Loss